Adaptation of goats feeding systems to the adverse economic conditions by changing the grazing management practices - Manousidis T.; Kyriazopoulos A.P.; Semenzato P.; Sturaro E.; Ramanzin M.; Ragkos A.; Abas Z. (Innovation for sustainability in sheep and goats, 2019)
The economic sustainability of the intensive sheep and goats systems in the Mediterranean region has been compromised by the current economic crisis, which has worsened the impacts of the high costs of purchased feeds and the high dependency on capital. An alternative option to overcome these issues is the extensification of farming systems which provides livestock farmers with the necessary flexibility to adjust their livelihoods according to the external circumstances. Thus, they can modify the grazing system, the daily grazing duration and the supplementation management according to the availability of necessary resources in order to achieve an acceptable level of flock productivity. The purpose of the present study was to investigate the shepherds grazing management practices and the characteristics of the flock’s movement in a communal rangeland. For this purpose, the case of a herded goat farm was investigated for three seasons (spring, summer and autumn) throughout two consecutive years during the economic crisis when the cost of feedstuffs increased and the selling price of milk decreased. Collars with GPS devices were placed on adult female goats’ neck for four consecutive days during each test period. The GPS data were analysed using GIS tools. According to the results grazing spatial patterns per season were differentiated as the shepherd took into account the cost of supplementation, the forage availability per season and criteria to prevent overgrazing.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)